Infectious Diseases Of The Nervous System (Eurasian Journal of Humanities and Social Sciences, 2025)
This article presents ideas about the causative agents of the disease, the organization of which, in most cases, children affected by neuroinfections such as meningitis, encephalitis, and meningoencephalitis, constitute the majority of students sent to special schools.